Enhanced photocatalytic activity of rGO-WO3 for hydrogen generation through copper oxide incorporation under sunlight irradiation - Aldo Kevin López-Matus; Viridiana Wendy Velázquez Vázquez; Karla María Aguilar-Casto; Edgar Vicente Macias-Melo; Getsemani Morales Mendoza; José Ysmael Verde Gómez; Rosendo López-González (Journal of Materials Science: Materials in Engineering)
Abstract The photocatalysis process using sunlight as an energy source is a promising alternative to produce hydrogen from the decomposition of water. For this purpose, the reduced graphene oxide (rGO) was synthesized by the Hummers method to increase the electronic transport. In the effort to create a composite with different energy levels, WO3 was used as a support that can absorb the sunlight and copper ions to induce effects (energetic sublevels) on the photocatalytic activity. Composites with different contents of rGO and WO3 were obtained by the hydrothermal process, and Cu1+ ions were coupled by the impregnation method. The resulting materials were characterized by spectroscopies Raman, ultraviolet visible (UV–Vis), and X-ray photoelectron (XPS) as well as scanning electron microscopy (FESEM), nitrogen sorption, and X-ray diffraction (XRD). From the parameters analyzed, the Raman results indicate that the highest content of reduced graphene oxide is associated with the strongest intensities in the 2D and G bands, which suggests the formation of a multilayered material. Incorporating 0.5% copper ions reduced the FWHM value of WO3, indicating higher crystallinity. The reduced graphene oxide enhances electronic transport on the photocatalytic surface. Additionally, copper ions serve as sites for electron capture, which prevents charge recombination. This process is reflected in an increase in interfacial charge transfer. The experimental results from a solar concentrator demonstrated that the composite material containing 0.5 wt.% copper and 6 wt.% reduced graphene oxide on tungsten trioxide (0.5Cu-6rGO-WO3) achieved the highest yield, producing 349 µmol/g after a reaction time of 5 h. In comparison, the bare WO3 produced only 272 µmol/g. The enhanced photocatalytic activity of the composite materials is attributed to their increased ability to absorb visible light, which stimulates the reduction reactions, as confirmed by optical analysis. The research reveals that utilizing a specific photocatalyst under a parabolic cylindrical solar concentrator offers a pathway for the generation of molecular hydrogen.